Association between severity of diabetic complications and risk of cancer in middle‐aged patients with type 2 diabetes - Yao‐Hsien Tseng; Yu‐Tse Tsan; Pau‐Chung Chen (Journal of Diabetes Investigation)
ABSTRACT Aim Hyperglycemia was found to be associated with an increased risk of cancer in a general population cohort. However, it remains to be established whether the severity of diabetic complications is associated with cancer risk in patients with diabetes. Materials and Methods We used the National Health Insurance Research Database from 2000 through 2013, including those with newly diagnosed diabetic patients (n = 616,742). We collected all vascular and metabolic complications to develop an adapted diabetic complication severity index (aDCSI), ranging from 0 to 13 annually, as proxies of the severity of diabetic complications and performed follow‐up from the onset of diabetes until incident cancer, death, or the study end. Results Within the mean follow‐up period of 9 years, the rates of cancer incidence per 100,000 person‐years were 815.2 vs 482.0 and 611.1 vs 358.9 for the top vs bottom quartiles, respectively, of aDCSI in men and women (adjusted HRs 1.17 (95% CI 1.10–1.25) and 1.20 (95% CI 1.10–1.30), respectively). The risk of cancer was 1.7‐ to 1.9‐fold for the top vs bottom quartiles of aDCSI in diabetic onset age of 40–44 (HRs 1.74 (95% CI, 1.39–2.18) in men and HRs 1.93 (95% CI, 1.39–2.66) in women). However, among patients with diabetic onset age of 60–64, the associations between the severity of diabetic complications and cancer risk were attenuated. Conclusions Patients with higher severity of diabetic complications have an increased risk of cancer compared to those with the lowest severity, particularly for those with earlier onset and greater severity of diabetic complications.